Latinoamérica y la cultura en el siglo XXI - Giesecke Sara Lafosse, Margarita (2002)
This study deals with Latin American culture from the perspective of history and as an essential theme to understand the complexity of the problem of underdevelopment. It examines what is meant by culture, traces the history of the formation of Latin American culture and points out the role that this should correspond to overcome underdevelopment in the context of a globalized world. He argues that communication democracy and education are the alternatives for the forging of cultural identities capable of negotiating with globalization.